Nudging tourists to donate for conservation: Experimental evidence on soliciting voluntary contributions for coastal management. (1st May 2019) - Nelson, Katherine M.; Partelow, Stefan; Schlüter, Achim
Abstract: This research examines the donation behavior of tourists who are asked to donate to coastal conservation aimed at addressing a bundled mix of land and sea issues. Historically, the governance and financing of land and sea conservation have been separated; yet coastal tourism directly involves a mix of activities and development challenges which link land and sea together on the coast. Marine parks, and numerous studies examining their funding schemes, have typically focused on mandatory user fees targeting specific types of activities. For example, many studies focus only on scuba divers' willingness to pay (WTP) for marine conservation. Alternative funding mechanisms, such as voluntary contributions, may be preferred, or even necessary, to traditional government imposed fees, but much less is known about effective implementation. Relatively few studies focus on bundled cross-boundary conservation activities (i.e., land and sea conservation) from all visitors of a marine park (i.e., beachgoers, surfers, boaters, snorkelers) and its encompassing coastal area. In this study we target tourists visiting a popular island and employ field experimental methods to explore the optimal donation request mechanism and pricing levels that influence real voluntary payments for conservation. The field experiment examines voluntary payments under the treatment conditions: open-ended, a set of several suggested donation amounts, and default opt-in and opt-out at two price levels. The field experiment was conducted with tourists on the island of Gili Trawangan, Indonesia. Results reveal that tourists are willing to donate to bundled land-sea conservation issues and that there is a significantly higher propensity to donate in all treatment conditions compared to the open-ended condition. The default opt-out conditions garnered the highest rate of donations at 75% and 62% respectively for the lower and higher set amounts. The mean donation amount was largest in the higher default opt-out condition. Our results suggest that the optimal method of requesting voluntary donations is a set default amount requiring users to opt-out if they do not wish to donate. Implementing a default opt-out eco-donation targeting all types of visitors represents a significant source of funding and illustrates the potential for donations to finance land and sea conservation efforts, an important avenue for future investigation in many interconnected systems that have been historically governed and financed separately. Highlights: We employ experimental methods to show how solicitation requests affect voluntary contributions to coastal conservation. Treatments: open-ended write-in, set of suggested donation amounts, default opt-in, and default opt-out at two price levels. The lower default opt-out condition represents the highest propensity to donate at 75%. Tourists are willing to donate to support services that sustainably manage coastal resources on Gili Trawangan.